Hydrogen generation from waste Mg based material in various saline solutions (NiCl2, CoCl2, CuCl2, FeCl3, MnCl2) - Figen, Aysel Kanturk; Coskuner, Bilge; Piskin, Sabriye (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
In the present study, waste Mg based material (W/Mg) was used as a raw material for the generation of hydrogen. Ball milling and saline solution method were performed to ensure full completion of the hydrolysis reaction. Improved texture properties were obtained by ball milling W/Mg for 15 h (2.29 m(2) g(-1) BET area, 11.94 mu m particle size). Ball milled W/Mg was used to generate hydrogen gas in the presence of various saline solutions (1 M NiCl2, CoCl2, CuCl2, FeCl3, and MnCl2). While hydrogen generation was not observed in pure water, maximum conversion (100%) was achieved in 1 M NiCl2 solution. Copyright (c) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen generation; Mg waste; Saline solution method; Ball milling; MAGNESIUM ALLOY SCRAPS; HYDROLYSIS; ALUMINUM; Chemistry; Electrochemistry; Energy & Fuels